2022
DOI: 10.3390/cells11213480
|View full text |Cite
|
Sign up to set email alerts
|

Genome Assessment of Carbapenem- and Colistin-Resistant Escherichia coli from Patients in a Sentinel Hospital in China

Abstract: Antimicrobial-resistant (AMR) pathogens are a significant threat to public health worldwide. However, the primary carrier of AMR genes, particularly against last-resort antibiotics, is still only partially studied in Chinese hospitals. In a sentinel hospital in China, we collected 157 E. coli strains from patients between January and July 2021. One blaNDM-1-, nine blaNDM-5-, and one mcr-1-positive E. coli recovered from inpatients were identified as resistant to meropenem and colistin. There are 37 virulence g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…It has been reported that IncX3 plasmids carrying bla NDM-5 are highly similar in various countries and host sources [29]. This suggests that these plasmids have the potential to e ciently disseminate bla NDM-5 among humans, animals, food, and the environment, thereby contributing to the rapid spread of bla NDM-5harboring isolates [30]. Various studies have reported different prevalence rates of the mcr-1 gene in E. coli isolates, ranging from 0.25% (10/3902) in Italy [31] to 1% in China [32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IncX3 plasmids carrying bla NDM-5 are highly similar in various countries and host sources [29]. This suggests that these plasmids have the potential to e ciently disseminate bla NDM-5 among humans, animals, food, and the environment, thereby contributing to the rapid spread of bla NDM-5harboring isolates [30]. Various studies have reported different prevalence rates of the mcr-1 gene in E. coli isolates, ranging from 0.25% (10/3902) in Italy [31] to 1% in China [32].…”
Section: Discussionmentioning
confidence: 99%
“…This result indicated that bacteria coharboring resistance genes and virulence factors are widespread, limiting antibiotic treatment. The astA gene has been identified in various DEC strains with outbreaks of diarrhea [ 66 , 67 , 68 , 69 ]. This study indicated that the astA gene might increase the strain’s virulence.…”
Section: Discussionmentioning
confidence: 99%
“…S1-PFGE was used to detect plasmid size in strains performed as previously described ( Ma et al, 2022a , b ; Tang et al, 2022b ). In brief, the plugs were made from the fresh cultures embedded in 2% gold agarose and lysed with cell lysis buffer.…”
Section: Methodsmentioning
confidence: 99%